ISOVALENT SUBSTITUTION OF LANTHANUM ATOMS IN BaLa2Sc2O7 SCANDATE: DOI: https://doi.org/10.17721/1728-2209.2023.1(58).4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. Exploring the effect of isomorphic substitution of atoms on structure and features of oxide compounds is one of the main tasks of modern materials science. Of particular interest are representatives of compounds An+1BnO3n+1 family (in particular, AIILn2Sc2O7 scandates) with slab perovskite-like snrucnure, which possess a number of practically important properties..This work is devoted to study the possibility of La atoms by smaller Dy atoms substitution in two-slab perovskite-like structure of BaLa2Sc2O7 and its effect on the crystallographic features of the BaLa2-xDyxSc2O7 scandates synthesized.Methods. The method of synthesis of new phases by heat treatment of co-crystallized salts, powder X-ray diffraction methods and the method of second optical harmonic generation by the obtained phases are used in the work.Results. The boundaries of isovalent substitution of La atoms (0 £ х £ 1,0) and the crystallographic parameters of the synthesized BaLa2-xDyxSc2O7 phases with a two-slab structure are determined. The indexing of the X-ray powder diffraction pattern of the BaLa2-xDyxSc2O7 (0 £ х £ 1,0) has revealed the tetragonal symmetry of the heat treated samples. The observed systematic extinctions and test results for the generation of a signal of the second optical harmonic of laser radiation indicate that their crystal structure belongs to centrosymmetrical P42/mnm space group. The character of the phase relations in the BaLa2-xDyxSc2O7 system and the type of concentration dependences the parameters of the tetragonal unit cells of BaLa2-xDyxSc2O7 phases with a two-slab structure indicate that by their nature these phases are limited row of solid solutions. The most probable mechanism of destruction of slab perovskite-like structure in samples BaLa2-xDyxSc2O7 with x > 1 was determined and a comparative comparison the stability of the slab structure of scandates AIILa2-xDyxSc2O7 (AII = Ba, Sr) was performed.Сonclusions. The obtained results indicate the possibility of a sufficiently significant isomorphic substitution of REE atoms in slab perovskite-like structure of BaLn2Sc2O7 scandates, can be further used to regulate their properties and are of undoubted interest for solving the problem of a targeted search new compounds of the type MeLnnBIIInO3n+1 with this type of structure.
Keywords: compounds of An+1BnO3n+1 type, slab perovskite-like structure, isomorphism, solid solution, X-ray powder diffraction.